Accelerated Osteogenic Orthodontics™ for retreatment of a patient with diminished root length and absence of the maxillary central incisor - Armando Montesinos F; Silvana Linares T; Marisol Pérez-Gasque B (Elsevier, 2015)
An 18-year-old female patient visited a university orthodontics department with a chief complaint of an unesthetic appearance of her teeth, including a protruded upper central incisor and unsatisfactory results from previous orthodontic treatment. Pretreatment records showed a Class II skeletal and dental relation with proclined upper and lower incisors, replacement of an absent upper left central incisor with the left upper cuspid, presence of the upper left deciduous cuspid, mild crowding, and 4 mm of overbite and overjet. The panoramic radiograph showed shortened roots of multiple teeth. Accelerated Osteogenic Orthodontics™ (AOO™) was recommended as an approach to reduce the treatment time and the risk of further root shortening. Despite being more expensive and requiring a surgical procedure, this treatment option was very attractive to the patient. The overall treatment time was 14 months. Facial balance was improved, and good occlusal relationships were achieved from the functional and esthetic perspectives. In conclusion, surgically facilitated orthodontics (specifically, AOO™) is an efficient and safe therapeutic tool for treating or retreating orthodontic patients with diminished root length. Keywords: Osteogenic accelerated orthodontics, Surgical facilitated orthodontics, Accelerated tooth movement, Diminished root length